2011
DOI: 10.1038/ja.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

Mycotrienin II, a translation inhibitor that prevents ICAM-1 expression induced by pro-inflammatory cytokines

Abstract: Pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-a and interleukin-1a (IL-1a), trigger the activation of the transcription factor nuclear factor-jB, a molecule that induces the expression of a variety of genes, including intercellular adhesion molecule-1 (ICAM-1). Here, we report that mycotrienin II, a member of the triene-ansamycin group, inhibited the cell-surface ICAM-1 expression induced by TNF-a more strongly than that induced by IL-1a in human lung carcinoma A549 cells. Mycotrienin II was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Human lung carcinoma A549 cells and human breast adenocarcinoma MCF‐7 cells were induced to express ICAM‐1 in response to IL‐1α stimulation [31,32]. A549 cells and MCF‐7 cells were preincubated with ursolic acid for 1 h and then incubated with IL‐1α for 6 h. Then, the amount of cell‐surface ICAM‐1 was quantitated by the Cell‐ELISA assay.…”
Section: Resultsmentioning
confidence: 99%
“…Human lung carcinoma A549 cells and human breast adenocarcinoma MCF‐7 cells were induced to express ICAM‐1 in response to IL‐1α stimulation [31,32]. A549 cells and MCF‐7 cells were preincubated with ursolic acid for 1 h and then incubated with IL‐1α for 6 h. Then, the amount of cell‐surface ICAM‐1 was quantitated by the Cell‐ELISA assay.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study indicated the expression of ICAM‐1 in the junctional epithelium but not in the oral gingival epithelium of germ‐free mice (12). The expression of ICAM‐1 in epithelial cells is regulated by proinflammatory cytokines such as IL‐1 and TNF‐α (28,29). Our study indicated the constitutive expression of these molecules in the junctional epithelium of germ‐free mice, whereas the oral sulcular epithelium showed almost no expression of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…33,34) We have recently shown that ouabain strongly inhibits the TNF-α-induced cell-surface expression of ICAM-1 in A549 cells. 26) Ouabagenin was found to inhibit the TNF-α-induced ICAM-1 expression in a dose-dependent manner; its IC 50 value was 7.5 µM (Fig.…”
Section: Cardenolide Aglycones Inhibit Namentioning
confidence: 99%
“…33,34) Cell-surface ICAM-1 (%) was calculated using the following formula: {(test sample−background)/(sample with TNF-α−background)}×100.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation